To the 190th anniversary of the Herbarium of V.N.Karazin Kharkiv National University (CWU) - б/а, б/а (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
To the 190th anniversary of the Herbarium of V.N.Karazin Kharkiv National University (CWU)